Glutamine synthetase: an unlikely case of functional redundancy in Arabidopsis thaliana. (4th March 2022) - Moreira, E.; Coimbra, S.; Melo, P.
Abstract: Glutamine synthetase (GS, EC 6.3.1.2) is an essential enzyme in plant metabolism, catalysing the assimilation of inorganic nitrogen into the amino acid glutamine. GS is a key enzyme in plant growth and has received special attention due to its recognized roles in plant nitrogen use efficiency and crop productivity. It occurs in plants as a collection of isoenzymes, located in the cytosol (GS1) and plastids (GS2), consistent with the multiplicity of roles played in plant metabolism. It is considered that the different isoenzymes, involved in a wide variety of physiological processes throughout the plant life cycle, perform non‐redundant and non‐overlapping roles. In fact, specific and non‐redundant roles of GS isoenzymes in nitrogen metabolism were observed in species like Oryza sativa and Zea mays . However, in A . thaliana the GS isoenzymes, five cytosolic and one plastidic, are suggested to have functional redundancy and an isoenzyme compensation mechanism, specific to this species, was described. This review integrates analyses on the likely roles of the distinct cytosol‐ and plastid‐located GS isoenzymes in A. thaliana, highlighting the redundancy of the GS gene family specifically occurring in this model plant. Abstract : Arabidopsis thaliana  revels a species‐specific functional redundancy of the Glutamine Synthetase gene family, having an isoenzyme compensation mechanism that prevents gene loss of function.